Neuroprotection by the Immunomodulatory Drug Pomalidomide in the Drosophila LRRK2WD40 Genetic Model of Parkinson’s Disease - Maria Antonietta Casu (Frontiers in Aging Neuroscience, 2020)
The search for new disease-modifying drugs for Parkinson’s disease (PD) is a slow and highly expensive process, and the repurposing of drugs already approved for different medical indications is becoming a compelling alternative option for researchers. Genetic variables represent a predisposing factor to the disease and mutations in leucine-rich repeat kinase 2 (LRRK2) locus have been correlated to late-onset autosomal-dominant PD. The common fruit fly Drosophila melanogaster carrying the mutation LRRK2 loss-of-function in the WD40 domain (LRRK2WD40), is a simple in vivo model of PD and is a valid tool to first evaluate novel therapeutic approaches to the disease. Recent studies have suggested a neuroprotective activity of immunomodulatory agents in PD models. Here the immunomodulatory drug Pomalidomide (POM), a Thalidomide derivative, was examined in the Drosophila LRRK2WD40 genetic model of PD. Mutant and wild type flies received increasing POM doses (1, 0.5, 0.25 mM) through their diet from day 1 post eclosion, until postnatal day (PN) 7 or 14, when POM’s actions were evaluated by quantifying changes in climbing behavior as a measure of motor performance, the number of brain dopaminergic neurons and T-bars, mitochondria integrity. LRRK2WD40 flies displayed a spontaneous age-related impairment of climbing activity, and POM significantly and dose-dependently improved climbing performance both at PN 7 and PN 14. LRRK2WD40 fly motor disability was underpinned by a progressive loss of dopaminergic neurons in posterior clusters of the protocerebrum, which are involved in the control of locomotion, by a low number of T-bars density in the presynaptic bouton active zones. POM treatment fully rescued the cell loss in all posterior clusters at PN 7 and PN 14 and significantly increased the T-bars density. Moreover, several damaged mitochondria with dilated cristae were observed in LRRK2WD40 flies treated with vehicle but not following POM. This study demonstrates the neuroprotective activity of the immunomodulatory agent POM in a genetic model of PD. POM is an FDA-approved clinically available and well-tolerated drug used for the treatment of multiple myeloma. If further validated in mammalian models of PD, POM could rapidly be clinically tested in humans.